A Community Needs Assessment of the Physical Activity and Food Environment in a Predominantly Hispanic U.S. City. (September 2016) - Lebron, Cynthia; Stoutenberg, Mark; Portacio, Francia; Zollinger, Terrell W.
Introduction: Hispanics suffer disproportionately compared with non-Hispanic Whites from health conditions that are affected by physical inactivity and poor dietary habits. Method: A needs assessment was conducted in Hialeah, Florida, the largest enclave of Cubans in the United States, to assess the perspectives of community stakeholders and members regarding the roles of physical activity and nutrition environments. Interviews were performed with community stakeholders ( n = 21), and responses were grouped into major themes. Surveys were conducted with community members ( n = 85). Descriptive analyses were used to categorize responses and potential differences across responses were explored. Results: Both community members and stakeholders reported that the local park system was a major asset to healthy living in Hialeah and agreed that traffic issues and a lack of walkability were major barriers to being physically active; however, there was variability in the response to the quality of the food environment. Conclusion: The perspectives of the community members and stakeholders will be valuable in highlighting pathways to enhancing the health and wellness of the residents of Hialeah.